Efforts To Improve Learning Outcomes Of Pencak Silat Kick Through Learning Modification In Grade VI Students Of SD Negeri Mojoroto 2, Kediri City In 2024/2025 - Elang Romadho; Nur Ahmad Muharram (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to improve the effectiveness of Pencak Silat learning through jejag kick training using stick media for six grade students at Mojoroto 2 Elementary School. The results showed a significant increase in learning. In Cycle I, the average student score increased from 3.1 at meeting I to 3.33 at meeting II. Meanwhile, in Cycle II, the average score increased from 3.23 at meeting I to 3.6 at meeting II. Teacher learning activities also improved, with teacher activity scores in Cycle I meeting I of 2.42 and increasing to 4.28 at meeting II. In Cycle II, teacher activity increased further with scores of 3.57 in round I and 4.71 in round II. In addition, the evaluation results showed an increase in student learning completeness. In Cycle I, the average student score was 74.43 with 35 students completing and 5 students not completing. In Cycle II, the average score increased to 74.94 with 39 students completing and only 1 student who had not achieved completion. Based on the results of this study, it can be concluded that the use of stick media in jejag kick training is effective in improving the quality of Pencak Silat learning, both in terms of student skills and teacher learning activities.